The influence of product knowledge and customer relationship marketing on interest customer buy at PT. RHB Sekuritas Indonesia Medan - Gultom, Pesta; Rezeki, Sri; Januarty, Widalicin; Sutantio, Andy (Jurnal Mantik, 2024)
This research aims to determine the influence of Product Knowledge and Customer Relationship Marketing on Customer Buying Interest at PT. RHB Securities Indonesia Medan. The research methodology used is a quantitative descriptive method. The research population that will be used in the research is all prospective customers who will make purchases from the company during the 2023 period, the exact number of which is not known. Due to the unknown population and bias in the number of consumers who make purchases, using the Hairs formula, 100 respondents were obtained, while the sampling technique was to use accidental sampling. The results of the research analysis show that the variable has a significant positive influence partially and simultaneously between Product Knowledge and Customer Relationship Marketing on customer buying interest at PT. RHB Securities Indonesia